2022
DOI: 10.1186/s13046-022-02542-8
|View full text |Cite
|
Sign up to set email alerts
|

EIF4A inhibition targets bioenergetic homeostasis in AML MOLM-14 cells in vitro and in vivo and synergizes with cytarabine and venetoclax

Abstract: Background Acute myeloid leukemia (AML) is an aggressive hematological cancer resulting from uncontrolled proliferation of differentiation-blocked myeloid cells. Seventy percent of AML patients are currently not cured with available treatments, highlighting the need of novel therapeutic strategies. A promising target in AML is the mammalian target of rapamycin complex 1 (mTORC1). Clinical inhibition of mTORC1 is limited by its reactivation through compensatory and regulatory feedback loops. Her… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 95 publications
(155 reference statements)
0
2
1
Order By: Relevance
“…In contrast to our study, investigations on AML cells obtained from patients illustrated related MMP resistance to oxidative phosphorylation instead of stemness of leukemia cells [35]. Mercier et al, showed that Ara-c did not affect the MMP of AML cells, which could be due to cell source, cell type, and Ara-C dosage [37].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to our study, investigations on AML cells obtained from patients illustrated related MMP resistance to oxidative phosphorylation instead of stemness of leukemia cells [35]. Mercier et al, showed that Ara-c did not affect the MMP of AML cells, which could be due to cell source, cell type, and Ara-C dosage [37].…”
Section: Discussioncontrasting
confidence: 99%
“…Results illustrated that the combination of a high dose of Ara-C with ½ EC 50 dose of 2-DG resulted in a signi cant boost in ROS compared to each drug alone. Many reports indicated that a combination of drugs could increase the effectiveness for example; the combinations of myeloperoxidase inhibitor and Cytarabine in leukemia cells [26], EIF4A inhibitor and Ara-c in MOLM-14 cell line [37], 2-DG with arsenic trioxide in AML derived cell line [40] and 2-DG and with l,3-bis(2-chloroethyl)-1-nitrosourea (BCNU) in glioblastoma cells [41]. However, there are some controversies to this for example combining Exotimer with 2-DG on HL-60 cells did not increase ROS [31].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we report on the development of MG-002, an orally available rocaglate capable of reducing primary tumor growth, blocking metastatic seeding, and potentiating the effects of DXR on suppression of metastatic growth. Finally, MG-002 is likely to exert cytotoxic effects in other malignancies given promising pre-clinical studies showing that other eIF4A inhibitors elicit strong anti-neoplastic effects in models of leukemia and pancreatic cancer ( 72 , 73 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, VEN-based therapies were approved by the Food and Drug Administration (FDA) for the treatment of AML patients who cannot receive intensive chemotherapy or who are older than 75 years of age [ 46 , 47 ]. Numerous studies have shown that the antileukemic activity of VEN is limited to combination therapies [ 48 , 49 ]. In this work, the combinatorial activity of TRAIL and VEN was assessed in AML cell lines and patient samples with high levels of TP53INP2, and this activity was validated in a PDX mouse model.…”
Section: Discussionmentioning
confidence: 99%